2021
DOI: 10.1108/ijchm-07-2020-0723
|View full text |Cite
|
Sign up to set email alerts
|

Experience perceptions, memorability and life satisfaction: a test and theory extension in the context of Oktoberfest

Abstract: Purpose Based on the Oktoberfest context and memory-dominant logic (MDL), the purpose of the study included assessing drivers of the perceptions of experience uniqueness; if these drivers and experience uniqueness perceptions transformed in memorable experiences; and if memorable experiences translated into enhanced life satisfaction. Based on these relationships, a typology and theory extension is provided integrating practical examples. Design/methodology/approach A five-factor model was tested using explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Meanwhile, emotions do not show a significant relationship with their dependent variable. It contradicts with few studies which stated, (i.e., Harrington et al (2021), Srinivas et al (2020), showing that emotion has affected the retirees' quality of life. These results could be justified as the majority of the respondents (72.4%) have just about one to five years, recently retired, and are mostly (73.3%) in a healthy condition.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Meanwhile, emotions do not show a significant relationship with their dependent variable. It contradicts with few studies which stated, (i.e., Harrington et al (2021), Srinivas et al (2020), showing that emotion has affected the retirees' quality of life. These results could be justified as the majority of the respondents (72.4%) have just about one to five years, recently retired, and are mostly (73.3%) in a healthy condition.…”
Section: Discussionmentioning
confidence: 62%
“…The researchers suggested that the preventive care approach may improve the quality of care and health and lower costs by adopting appropriate quality improvement strategies that may aid preventive care. Harrington et al (2021) recently investigated if memorable experiences translated into enhanced life satisfaction during the Oktoberfest event, one of the hospitality businesses serving food and drink. Their findings showed that meaningfulness and memorability had a significant positive effect on their life satisfaction, and it also partially mediated the relationship with experience uniqueness.…”
Section: Emotionmentioning
confidence: 99%
“…Facebook, Youtube, Tik Tok). It is found that attendees with more prior engagement have a more positive perception of the actual experience (Harrington et al , 2021). Information communication technologies such as augmented reality may also be applied to such programs to enhance audience experience and construct memorable experience (Olya et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have attempted to link GTE to QOL constructs, the extant literature lacks a fully integrated model with relevant and enhanced constructs (Harrington et al , 2021; Hernández-Mogollón et al , 2020). This model includes three dimensions of each of the food-related lifestyle (FRL) and the leisure attitude as precursor of the remembered consumption experience (CEX) based on a GTE, the focal construct of this study.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%